(untitled) (Global Journal of Science Frontier Research, 2019)
Compounds pos sessing a m ethylene bridge located between two strong electron withdrawing groups (MACs,e.g., diketones, dinitriles, benzoyl acetonitriles, cyanothioacetamide, ethyl acetoacetate, diethyl malonate ethyl cyanoacetate, cyanoanilides, etc.) have also been of significant interest in coordination and organomettalic chemistry of hydrazones, for instance,diketones are important starting materials in many organic synthetic reactions, particularly in the perfume and cosmetic industries.